Combining Modulated Techniques for the Analysis of Photosensitive Devices. Issue 10 (3rd September 2021) - Alvarez, Agustin O.; Ravishankar, Sandheep; Fabregat‐Santiago, Francisco
Abstract: Small‐perturbation techniques such as impedance spectroscopy (IS), intensity‐modulated photocurrent spectroscopy (IMPS), and intensity‐modulated photovoltage spectroscopy (IMVS) are useful tools to characterize and model photovoltaic and photoelectrochemical devices. While the analysis of the impedance spectra is generally carried out using an equivalent circuit, the intensity‐modulated spectroscopies are often analyzed through the measured characteristic response times. This makes the correlation between the two methods of analysis generally unclear. In this work, by taking into consideration the absorptance and separation efficiency, a unified theoretical framework and a procedure to combine the spectral analysis of the three techniques are proposed. Such a joint analysis of IS, IMPS, and IMVS spectra greatly reduces the sample space of possible equivalent circuits to model the device and allows obtaining parameters with high reliability. This theoretical approach is applied in the characterization of a silicon photodiode to demonstrate the validity of this methodology, which shows great potential to improve the quality of analysis of spectra obtained from frequency domain small‐perturbation methods. Abstract : A unified procedure is proposed for analyzing impedance, intensity‐modulated photocurrent, and photovoltage spectroscopies. This procedure allows the accurate selection of the equivalent circuit and results in a high quality of parameters obtained from fitting of the spectra. An experimental application of the procedure is presented for a silicon photodiode.